Dorsal Wrist Spanning Plate Fixation for Treatment of Radiocarpal Fracture-Dislocations. (November 2021) - Wahl, Elizabeth P.; Lauder, Alexander S.; Pidgeon, Tyler S.; Guerrero, Evan M.; Ruch, David S.; Richard, Marc J.
Background: Radiocarpal dislocations are rare injuries that result from high-energy forces across the wrist with the hallmark finding of radiocarpal ligament disruption. Published treatment methods are comprehensive with moderate-to-good outcomes. The purpose of this study was to review the treatment of radiocarpal dislocations with a dorsal wrist spanning plate.Methods: A retrospective review was conducted analyzing the radiographic and clinical outcomes of patients treated for a radiocarpal dislocation using a dorsal wrist spanning plate over a 10-year period. Outcomes assessed included radiographic joint incongruity and arthrosis, wrist range of motion, grip strength, Visual Analogue Scale (VAS) score, surgical complications, and Disabilities of the Arm, Shoulder, and Hand (DASH) score.Results: Thirteen patients were treated with a dorsal wrist spanning plate for radiocarpal dislocation with a mean follow-up of 615 days from the time of initial surgery. Six patients (46%) had associated distal radioulnar joint instability. The mean wrist range of motion at the final follow-up was: flexion 39°, extension 44°, pronation 79°, and supination 84°. One patient (8%) developed ulnar translation of the carpus, and 11 patients (85%) developed radiographic posttraumatic wrist arthrosis. Mean VAS and DASH scores were 4 and 18, respectively.Conclusions: Acute treatment with a dorsal wrist spanning plate in this series resulted in comparable outcomes to what have been previously reported in the literature. The dorsal wrist spanning plate offers the surgeon a reliable method of stabilization, with minimal additional surgical trauma to the wrist, while avoiding the potential for infections that develop with other treatment methods.